Characterizing the Mobile Microtask Writing Process - August, Tal; Iqbal, Shamsi; Gamon, Michael; Encarnación, Mark (MobileHCI, 2020)
The unique limitations of mobile environments make content creation and editing difficult. Microtasking—breaking down complex tasks into subtasks—requires shorter attention spans and quick interactions, making it suitable for mobile usage scenarios. Writing is an ideal process for mobile microtasking because of its many subgoals, but little is known about how writers can use this decomposition through the evolution of a document. In this paper we present findings from a controlled, week long study to characterize how writers use mobile microtasks while authoring a document. We found that writers created microtasks for editing and inserting information that generally required minimal writing. These tasks were especially well suited for mobile devices with writers completing tasks on commutes or while waiting for meetings. Writers who microtasked found it easy to interact with their document and complete tasks, writing and editing their document more overall compared to writers who instead edited their document directly on their phone.